Landscape diversity influences the arthropod species diversity in the rice field - Ali, M. P.; Biswas, M.; Clemente-Orta, Gemma; Kabir, M. M. M.; Datta, Juel; Haque, S. S.; Qin, Xinghu; Landis, Douglas; Kaur, Parwinder; Pittendrigh, Barry R.; Howlader, M. T. H. (Frontiers in Environmental Science, 2022)
Landscape diversity is one of the key drivers for maintaining ecosystem services in agricultural production by providing vital habitats and alternative food sources for beneficial insects and pollinators within the agricultural landscapes. The landscape structure, land uses and diversity differ between geographic locations. However, how the changes of landscape structure and land use diversity affect the arthropod diversity in a geographic area is poorly understood. Here we tested the the impact of landscape diversity on the rice farmland arthropod diversity in three geographic locations of Bangladesh. The landscape in Chattogram has intensified with mixed nature and land use mix (LUM) shows highly diversified to very highly diversity (>7.9). But this landscape is modified in Satkhira and visualized in LUM index where 80% grids under highly diversified (0.59–0.79) and landscape changes in Patuakhali portrayed the LUM index from moderately (0.39–0.59) to less diversified (0.19–0.39). These significant different landscape diversities influenced the arthropod diversity in rice field. Arthropod species diversity increases with the increasing of LUM index. Maximum tillering stage of rice growth harbored higher abundance and species diversity in rice field. Moreover, we found vegetation is the most important factor influencing the abundance of arthropods. Extensive agriculture and forest contributed substantially to predicting the arthropod richness. Meanwhile, barren land and high density residential as well as intensive agriculture had large impacts on the species diversity. This study indicates that landscape diversity plays a vital role to shape the species diversity in rice field, providing guidelines for considering the local landscape approach to plan for conservation of arthropod diversity for maximising natural pest control ecosystem service in crop production.